2013
DOI: 10.5888/pcd10.130035
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Services Capacity for Prehospital Stroke Care in North Carolina

Abstract: IntroductionPrior assessments of emergency medical services (EMS) stroke capacity found deficiencies in education and training, use of protocols and screening tools, and planning for the transport of patients. A 2001 survey of North Carolina EMS providers found many EMS systems lacked basic stroke services. Recent statewide efforts have sought to standardize and improve prehospital stroke care. The objective of this study was to assess EMS stroke care capacity in North Carolina and evaluate statewide changes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, the Utstein recommendations for emergency stroke care stressed the importance of a population-based stroke registry collecting data across the stroke chain of survival, including prehospital data on prenotification 33 . With prior research suggesting a disconnect between EMS prenotification policy and practice, 18 such stroke registries should be designed and executed to facilitate bidirectional data sharing and communication between EMS and hospitals 34 . This systems approach and collaboration have the potential to improve acute stroke care in underserved settings and address stroke disparities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Utstein recommendations for emergency stroke care stressed the importance of a population-based stroke registry collecting data across the stroke chain of survival, including prehospital data on prenotification 33 . With prior research suggesting a disconnect between EMS prenotification policy and practice, 18 such stroke registries should be designed and executed to facilitate bidirectional data sharing and communication between EMS and hospitals 34 . This systems approach and collaboration have the potential to improve acute stroke care in underserved settings and address stroke disparities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of national data from a hospital-based stroke quality improvement program observed that 57% of EMS arrivals were prenotified, which did not change from 2014 to 2019 17 . A statewide survey of EMS agencies in North Carolina found that 98% of agencies reported a stroke prenotification policy; however, fewer than half reported communicating prehospital stroke screen results to the receiving hospital, suggesting a disconnect between policy and practice 18 . Although previous research has clearly shown that lower socioeconomic status (SES) and rural communities have poorer stroke 19 and other health outcomes, 20,21 these disparities in prehospital stroke care, specifically EMS prenotification, are understudied.…”
mentioning
confidence: 99%
“…PCD published articles of winning student manuscripts from 2011 through 2015 and in 2017 and 2018. From 2011 through 2015, manuscripts were screened and reviewed by a panel of peer reviewers who identified an overall winner whose manuscript was ultimately published (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Because of the tremendous response from students, we expanded submission screening, peer reviewing, and publishing to 5 student levels in 2017 and 2018, and winners were identified at the high school, undergraduate, graduate, doc-toral, and postdoctoral levels (1,12).…”
mentioning
confidence: 99%
“…16 In North Carolina, to improve timely access to stroke care, emergency medical services (EMS) transport destination plans allow bypassing a local community hospital for a primary stroke center. [17][18][19] Furthermore, ongoing research is investigating the benefit of direct transport of acute stroke patients to an endovascular-capable hospital based on symptom onset and severity. [20][21][22][23] Many stroke centers use a network of hospitals for providing telemedicine and facilitating interfacility transfers with community hospitals.…”
mentioning
confidence: 99%